Application of Personalized Navigation Templates to Oxford Single Condylar Replacement in a Chinese Population - Gan, Yudong; Zhuang, Jian; Jiang, Wenxiao; Sun, Wei; Zhang, Yijun (The Journal of Knee Surgery, 2020)
The purpose of this study is to develop and validate a novel patient-specific navigational template for unicompartmental knee arthroplasty (UKA). A total of 120 patients who underwent UKA were randomized and divided into the conventional method and navigational template groups. In the navigational template group, patient-specific navigational templates were designed and used intraoperatively to assist 60 patients with UKA. Information on operation time and blood loss was recorded by an independent operating room nurse. After surgery, the positions of the prostheses were evaluated using X-rays. All navigation templates were found to fit its corresponding biomodel appropriately without any free movement. The navigational template exhibited significantly better accuracy than the conventional method. Statistically significant differences in the femoral prosthesis flip angle, femoral prosthesis flexion angle, and tibial plateau varus and valgus angle were observed between the two groups (p = 0.022, 0.042, 0.043, respectively). In addition, the mean operation time was statistically and significantly lower in the navigational template group than in the conventional group (p = 0.035). This study introduces a novel navigational template to UKA, the accuracy of which is proven by clinical operation. This is a Level III, therapeutic study.
Keywords: unicompartmental knee arthroplasty; navigation template; Oxford